2021
DOI: 10.1371/journal.pone.0258356
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on trade flows: Measuring their impact through government policy responses

Abstract: This paper examines the impact of COVID-19 on bilateral trade flows using a state-of-the-art gravity model of trade. Using the monthly trade data of 68 countries exporting across 222 destinations between January 2019 and October 2020, our results are threefold. First, we find a greater negative impact of COVID-19 on bilateral trade for those countries that were members of regional trade agreements before the pandemic. Second, we find that the impact of COVID-19 is negative and significant when we consider indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 67 publications
(70 reference statements)
1
46
0
2
Order By: Relevance
“…The impact of COVID-19 was damaging on all economies, whether developed, less developed or transitioning, as in the case of the V4 countries. The global effect can be detected in the development of major macroeconomic indicators, as well as health and social indicators, around the world (e.g., Vidya and Prabheesh 2020;Anand et al 2020;Barbero et al 2021;Jindřichovská and U gurlu 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The impact of COVID-19 was damaging on all economies, whether developed, less developed or transitioning, as in the case of the V4 countries. The global effect can be detected in the development of major macroeconomic indicators, as well as health and social indicators, around the world (e.g., Vidya and Prabheesh 2020;Anand et al 2020;Barbero et al 2021;Jindřichovská and U gurlu 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Their results revealed that an increase in COVID-19 cases leads to a rise in the export of capital and consumption products among Malaysia and its trading partners. Barbero et al ( 2021 ) scrutinized the effect of COVID-19 on trade based on the state-of-the-art gravity technique and the data of 68 countries over the period of January 2019–October 2020. The empirical findings indicate different aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, losses of food production in one sector (e.g., crops, livestock, aquaculture, fisheries) due to geographically localized shocks create challenges not only within the same sector and geographic region, but also across sectors and regions (Cottrell et al 2019 ). Global shocks, such as the COVID-19 pandemic, exacerbate or amplify these effects, although their consequences (some of which are not necessarily negative) are highly variable depending on the degree of interconnectedness (Barbero et al 2021 ; Dudek and Śpiewak 2022 ). Thus, it is crucial to evaluate the influence of these global shocks on the evolution of global interconnectedness.…”
Section: Introductionmentioning
confidence: 99%